Benthic ammonia oxidizers differ in community structure and biogeochemical potential across a riverine delta - Damashek, Julian; Smith, Jason M.; Mosier, Annika C.; Francis, Christopher A. (Frontiers in Microbiology, 2015)
Nitrogen pollution in coastal zones is a widespread issue, particularly in ecosystems with urban or agricultural watersheds. California’s Sacramento-San Joaquin Delta, at the landward reaches of San Francisco Bay, is highly impacted by both agricultural runoff and sewage effluent, leading to chronically high nutrient loadings. In particular, the massive discharge of ammonium into the Sacramento River has altered this ecosystem by increasing ammonium concentrations and thus changing the stoichiometry of inorganic nitrogen stocks, with potential effects throughout the food web. To date, however, there has been little research examining N biogeochemistry or N-cycling microbial communities in this system. We report the first data on benthic ammonia-oxidizing microbial communities and potential nitrification rates for the Sacramento-San Joaquin Delta, focusing on the functional gene amoA (encoding the α-subunit of ammonia monooxygenase). There were stark regional differences in ammonia-oxidizing communities, with ammonia-oxidizing bacteria (AOB) outnumbering ammonia-oxidizing archaea (AOA) only in the ammonium-rich Sacramento River. High potential nitrification rates in the Sacramento River suggested these communities may be capable of oxidizing significant amounts of ammonium, compared to the San Joaquin River and the upper reaches of San Francisco Bay. Gene diversity also showed regional patterns, as well as phylogenetically unique ammonia oxidizers in the Sacramento River. The community structure and biogeochemical function of benthic ammonia oxidizers appears related to nutrient loadings. Unraveling the microbial ecology and biogeochemistry of N cycling pathways is a critical step toward understanding how such ecosystems respond to the changing environmental conditions wrought by human development and climate change.